(untitled) (Fiep Bulletin - online, 2014)
Exposure to formaldehyde is a common practice in hair salons, its application in hair treatments for straightening, neglects the health of consumers. There is a relationship between the concentration and the symptoms caused by such exposure. Formaldehyde is allowed only in hair cosmetics products with a preservative function, during manufacture of the product with maximum concentration of 0.2%. This is a study consisting of 196 randomly chosen women, the subjects answered a questionnaire consisting of 23 questions. This study aims to evaluate the perceptions of health, involvement of toxic effects during and after the procedure and knowledge of those involved regarding the toxicological effects when it is done improperly. Our results show that 71.43% interviewees have had progressive brush, effects on the eyes prevailed with 61.43%, there were also dermatologic reactions (27.86%) and a reaction caused by smoke during the procedure (40.00%). 76.53% the interviewees have knowledge of all or part of ANVISA Resolution 162 from 2001. It is concluded that the obtained results suggest the addition of formaldehyde in hair care products, and despite the knowledge of the established rules, there is a high rate of unconcern for the product used, whether or not the professional or the manufacturer adds formaldehyde in the preparation and toxicity levels of exposure.